The relationship between clinical parameters and the risk of mortality or requiring the insertion of a pacemaker in patients with bifascicular block - Mitchell, DC; Doubell, AF; Moses, J (SA Heart Journal, 2026)
Introduction: Patients with bifascicular block (BFB) are at risk of progressing to high-degree atrioventricular block (AVB) and have a higher mortality risk. This study aimed to identify relationships between clinical parameters in patients with BFB and the risk of mortality and/or requiring permanent pacemaker (PPM) insertion, to better risk-stratify and appropriately investigate patients at the time of diagnosis in a resource-limited setting. Method: A descriptive study was conducted via retrospective review of all patients who received an electrocardiogram (ECG) during 2014 at Tygerberg Hospital (TBH), South Africa. In total, 16 280 ECGs were assessed, accounting for 11 881 patients (some patients had more than 1 ECG), and those with BFB were identified. Patients’ records were assessed at the time of diagnosis and followed for 10 years to identify relationships between clinical parameters in patients with BFB and mortality or requiring a PPM. Results: Of the 11 881 patient ECGs assessed, 140 patients with BFB were identified. The mean age at diagnosis was 62 ± 17 years. Of these patients, 37 (26%) died, and 9 (6%) required a PPM. The mean age at diagnosis of demised patients was 66 ± 12 years (p = 0.07). Significant relationships with mortality included diabetes mellitus (DM) (p = 0.04) and a reduced left ventricular ejection fraction (LVEF) (p = 0.05), with age and hypertension related at a lower level of significance (p = 0.07 and p = 0.06, respectively). Significant relationships with PPM insertion were symptom presence at diagnosis (p ≤ 0.01) and PR interval prolongation at a lower level of significance (p = 0.08). Conclusion: In patients with BFB, DM, hypertension, age, and a reduced LVEF had the most significant relationships with mortality. Symptoms and a prolonged PR interval had the most significant relationships with requiring a PPM. Mortality in patients with BFB is more likely to be related to standard risk factors, such as DM, hypertension, age, and a reduced LVEF, than the conduction defect per se.